1998
DOI: 10.1007/s101200050006
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and prognostic factors in 10 783 patients with gastric cancer

Abstract: Abstract:Background. Although the results of gastric cancer treatment have markedly improved, this disease remains the most common cause of cancer death in Korea. Methods. Clinicopathologic characteristics were analyzed for 10 783 consecutive patients who underwent operation for gastric cancer at the Department of Surgery, Seoul National University Hospital, from 1970 to 1996. We also evaluated survival and prognostic factors for 9262 consecutive patients operated from 1981 to 1996. The clinicopathologic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
160
1
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(187 citation statements)
references
References 24 publications
19
160
1
7
Order By: Relevance
“…However, there has been enough proof that the prognosis of patients with >15 positive lymph nodes is significantly worse than that of patients with 7 to 15 positive lymph nodes. 17,22,23 In contrast, the RR of the sixth edition pN classification increased with regular intensity according to the increment of the pN classification, and was even comparable to the degree of the RR of the seventh edition pT classification. The seventh edition of the TNM classification demonstrated significant differences in the survival rate for each stage of disease despite a more complicated structure in comparison with the sixth edition staging system.…”
Section: 13mentioning
confidence: 84%
“…However, there has been enough proof that the prognosis of patients with >15 positive lymph nodes is significantly worse than that of patients with 7 to 15 positive lymph nodes. 17,22,23 In contrast, the RR of the sixth edition pN classification increased with regular intensity according to the increment of the pN classification, and was even comparable to the degree of the RR of the seventh edition pT classification. The seventh edition of the TNM classification demonstrated significant differences in the survival rate for each stage of disease despite a more complicated structure in comparison with the sixth edition staging system.…”
Section: 13mentioning
confidence: 84%
“…It is generally accepted that there is greater benefit in survival from LNs standardized dissections (11) . Many studies have shown that the number of LNs dissected is closely related to postoperative pathological tumor staging and prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Maruyama [81] examined 4734 patients treated at the National Cancer Center in Japan and indicated that the most important prognostic factors for gastric cancer patients were depth of invasion (relative risk, 4.69), lymph node metastasis (4.04), gross type (1.76), location (1.50), and histologic type (1.16). Kim et al [82] analyzed 10 783 patients who underwent operation at the Seoul National University Hospital, and demonstrated that independent prognostic factors in gastric cancer were curability (relative risk, 3.67), depth of invasion (2.18), and lymph node metastasis (2.06). Thus, the studies are unanimous in terms of the prognostic importance of the depth of invasion and status of lymph node metastasis [23,83,84].…”
Section: Prognostic Factorsmentioning
confidence: 99%